Ngô Tấn Đạt
12 tháng 3 2017 lúc 20:50

\(2ab=a+b\\ \Rightarrow 4ab=2a+2b\\ \Rightarrow4ab-2a-2b=0\\ \Rightarrow2a\left(2b-1\right)-\left(2b-1\right)=1\)

\(\Rightarrow\left(2a-1\right)\left(2b-1\right)=1\)

\(\Rightarrow a=b=1;0\)

Bình luận (0)
Đinh Đức Hùng
Tân binh -
12 tháng 3 2017 lúc 20:18

\(2ab=a+b\)

\(\Leftrightarrow a-2ab+b=0\)

\(\Leftrightarrow2a-2.2ab+2b=0\)

\(\Leftrightarrow2a-2b\left(2a-1\right)=0\)

\(\Leftrightarrow2a-1-2b\left(2a-1\right)=-1\)

\(\Leftrightarrow\left(2a-1\right)\left(1-2b\right)=-1\)

\(\Rightarrow2a-1=-1\) thì \(1-2b=1\) \(\Rightarrow a=0\) thì \(b=0\) (TM)

\(\Rightarrow2a-1=1\) thì \(1-2b=-1\) \(\Rightarrow a=1\) thì \(b=1\) (TM)

Vậy ( a;b ) = { (0;0) ; (1;1) }

Bình luận (0)

Các câu hỏi tương tự

Khoá học trên OLM của Đại học Sư phạm HN

Loading...

Khoá học trên OLM của Đại học Sư phạm HN